2011
DOI: 10.1007/s00401-011-0935-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition to peripheral nerve neoplasia: diagnostic criteria and pathogenesis of neurofibromatoses, Carney complex, and related syndromes

Abstract: Neoplasms of the peripheral nerve sheath represent essential clinical manifestations of the syndromes known as the neurofibromatoses. Although involvement of multiple organ systems, including skin, central nervous system and skeleton, may also be conspicuous, peripheral nerve neoplasia is often the most important and frequent cause of morbidity in these patients. Clinical characteristics of neurofibromatosis type 1 (NF1) and neurofibromatosis type 2 (NF2) have been extensively described and studied during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 115 publications
1
67
0
2
Order By: Relevance
“…It was also reported that formin (mDia) family proteins might mediate the disease progression role of the adenomatous polyposis coli familial colon cancer tumor suppressor gene (Wen et al, 2004). We analyzed NF2 and or SMARCB1 in case 3, but we could not find any mutation leading to schwannomatosis (DeWard et al, 2010;Rodriguez et al, 2012). Schwannomatosis should be remarked as a complication in further case carrying INF2 mutation.…”
Section: Inf2 Mutations In Charcot-marie-tooth Disease Complicated Wimentioning
confidence: 82%
“…It was also reported that formin (mDia) family proteins might mediate the disease progression role of the adenomatous polyposis coli familial colon cancer tumor suppressor gene (Wen et al, 2004). We analyzed NF2 and or SMARCB1 in case 3, but we could not find any mutation leading to schwannomatosis (DeWard et al, 2010;Rodriguez et al, 2012). Schwannomatosis should be remarked as a complication in further case carrying INF2 mutation.…”
Section: Inf2 Mutations In Charcot-marie-tooth Disease Complicated Wimentioning
confidence: 82%
“…Plexiform and cellular variants of schwannomas are also observed in NF2 patients, while melanotic schwannoma is not observed in NF2 and its psammomatous variant is correlated with the Carney complex [26]. Cellular schwannoma, commonly affecting paraspinal sites, is encapsulated entirely composed of Antoni A areas without Verocay bodies, with preserved pericellular reticulin.…”
Section: Neurofibromatosis Type 2 (Central Neurofibromatosis)mentioning
confidence: 99%
“…She was also noted to have no new lesions at that time. discussion Schwannomatosis is a rare disease characterized by the development of multiple schwannomas 11,18,22 and meningiomas. 14 The present case is a particularly aggressive case and is associated with a novel mutation in the SMARCB1 gene.…”
mentioning
confidence: 99%